Nilai Tambah pada Tindakan Pascapanen Curing, Pengeringan Askip dan Penyimpanan Bawang Merah Tingkat Petani (Studi Kasus Kabupaten Cirebon) (Added Value of Curing Treatment, Askip Drying, and Postharvest of Shallot in Farmers) - Sazli Tutur Risyahadi; Emmy Darmawati; Y Aris Purwanto (IPB University, 2014)
Added value of curing treatment, askip drying and storing are used for knowing the benefit of shallot postharvest process. Postharvest technique of shallot makes longer shelflife but adds cost. The method adopted in the study relied on informal interview with key informants and a number of participants at different stages of postharvest chain including the producers of shallot. Data was calculated by Hayami method. The results of the study showed that curing process has losses up to 20% and margin at Rp 1.050. The storage of shallot showed different margin between conventional and cold storage. There is higher margin of cold storage than conventional. Loss at cold-storage is only 15%for 2 months. Cold-storage margin is Rp 4.025 per kg, higher than the conventional one, which is only Rp 725 per kg.Keywords : added value analysis, Hayami method, postharvest of shallot